If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 4 = 5y + -1x Reorder the terms: 4 + 5y = 5y + -1x Reorder the terms: 4 + 5y = -1x + 5y Add '-5y' to each side of the equation. 4 + 5y + -5y = -1x + 5y + -5y Combine like terms: 5y + -5y = 0 4 + 0 = -1x + 5y + -5y 4 = -1x + 5y + -5y Combine like terms: 5y + -5y = 0 4 = -1x + 0 4 = -1x Solving 4 = -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 4 + x = -1x + x Combine like terms: -1x + x = 0 4 + x = 0 Add '-4' to each side of the equation. 4 + -4 + x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + x = 0 + -4 x = 0 + -4 Combine like terms: 0 + -4 = -4 x = -4 Simplifying x = -4
| 27x^7-24x^5/3x^3 | | 5y+4=5y+x | | 12+2=-2(7x-7) | | -.5x+1=7 | | 4(5n-1)+16=12-3(4-2n) | | 12x^1/x² | | 5b+3+6=19 | | 3/2v=16 | | (x+2)(x-2)=(2x+1)(x-2) | | 2x-(4x-9)=6-x | | 2x-35=27 | | 5x+3(4-6x)=11 | | 5/11=u/10 | | 8y-3=-4y+6 | | 2x-35=37 | | 2x^2+13x+8=2 | | f(a-4)=5x+2 | | 4/5k-6 | | 4/5k--6 | | 100=6x+4 | | 3x+-3=-9 | | 7.3=8.5-0.6x | | 15=8x+3-6 | | -6y=1/4 | | (2x-4)*x=100 | | 3x/(x^2-x-20) | | 3x/x^2-x-20 | | 1nx=6 | | 2x-4*x=100 | | C=8pieg | | y=-3z-4 | | 1/(3y)=1/24 |